“R1 Nightmares”: A resident-led on-call medical emergency simulation course for junior residents - McKenzie, Erica D; Sugarman, Jordan; Savage, Tyson; Lee, Matthew; Thornton, Hayley; Chaplin, Timothy; Altabbaa, Ghazwan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Implication StatementOn-call medical emergencies can be a source of anxiety for junior medical residents. Senior resident teachers are well-positioned to teach a safe approach to managing on-call emergencies, and simulation-based training has educational and patient safety advantages. We describe the implementation of a resident-facilitated, on-call emergency simulation course for first-year residents. The course was low-cost, time-efficient, increased residents’ self-rated comfort with acutely deteriorating patients and was highly recommended by participants. The “R1 Nightmares” course could be adapted for other residency programs and institutions.